2008
DOI: 10.1111/j.1360-0443.2008.02219.x
|View full text |Cite
|
Sign up to set email alerts
|

What did you drink yesterday? Public health relevance of a recent recall method used in the 2004 Australian National Drug Strategy Household Survey

Abstract: Aim-To (i) compare the Yesterday method with other methods of assessing alcohol use applied in the 2004 Australian National Drug Strategy Household Survey (NDSHS) in terms of extent of underreporting of actual consumption assessed from sales data and (ii) illustrate applications of the Yesterday method as a means of variously measuring the size of an Australian "standard drink", extent of risky/high risk alcohol use, unrecorded alcohol consumption and beverage specific patterns of risk in the general populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 16 publications
4
94
0
Order By: Relevance
“…Misperception may be an artefact of the underestimation of personal consumption, through lack of knowledge or self presentational bias (e.g. Stockwell et al, 2008). Perkins (2012 asserts that students 'do not, on average, under-report their own consumption'.…”
Section: Introductionmentioning
confidence: 99%
“…Misperception may be an artefact of the underestimation of personal consumption, through lack of knowledge or self presentational bias (e.g. Stockwell et al, 2008). Perkins (2012 asserts that students 'do not, on average, under-report their own consumption'.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, all alcoholic beverages are required to state on the label the number of standard drinks they contain. Nevertheless, a study showed that the alcohol content of drinks is larger than the defined standard drink (Stockwell et al, 2008). The study showed that the amount of ethanol in a typical Australian standard drink is 12.8 g compared with 10 g in an official Australian standard drink.…”
Section: Discussionmentioning
confidence: 94%
“…Despite the attempts of public health measures to curb excessive drinking, consumption levels remain high, often due to heavy episodic or 'binge' drinking (Gilligan et al 2012, Scottish Government 2012, Glock et al 2015. While there are well-documented concerns about the accuracy of selfreport estimates (Stockwell et al 2008, Burns et al 2010 there is also general agreement that consumption levels are high and indeed Scotland has among the highest rates of consumption and of alcohol-related deaths in Europe (Cook 2012). The gender gap which had seen high consumption as more a problem for men has narrowed in younger drinkers (Guise & Gill 2007, Scottish Government 2015a.…”
Section: Introductionmentioning
confidence: 99%